Proceedings of the International Conference on Management, Accounting, and Economy (ICMAE 2020) 2020
DOI: 10.2991/aebmr.k.200915.075
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Consequences of Brand Authenticity

Abstract: Brand Authenticity is essential for luxury brands. This study aims to explore the consequences of Brand Authenticity in luxury brands. Furthermore, it will analyse the effect of Brand Relationship Quality and Brand Trust toward Purchase Intention for data collection; this study conducts a survey that generates 280 datasets and used SEM to test the hypotheses. The results demonstrate that Brand Authenticity positively effects Brand Relationship Quality, and Brand Trust and brand trust have an impact on purchase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The results of Al-Meshal et al's (2020) research revealed that brand authenticity has a positive effect on purchase intention and that agree with the researchers' result. Also, Pratomo and Magetsari (2020) has proven that purchase intention is a consequence of Brand Authenticity. Additionally, Brand credibility has a positive effect on purchase intention as the result of this study (Kemp & Bui, 2011).…”
Section: 5) Discussion and Conclusionmentioning
confidence: 99%
“…The results of Al-Meshal et al's (2020) research revealed that brand authenticity has a positive effect on purchase intention and that agree with the researchers' result. Also, Pratomo and Magetsari (2020) has proven that purchase intention is a consequence of Brand Authenticity. Additionally, Brand credibility has a positive effect on purchase intention as the result of this study (Kemp & Bui, 2011).…”
Section: 5) Discussion and Conclusionmentioning
confidence: 99%
“…Usually, the brands kept in the consumer's memory are the preferred brand tendencies [14]. Brand awareness includes recall, recognition, always remembering the brand, purchase, and consume [15]- [18].…”
Section: All Variables Were Measured By Participants' Responses To Qu...mentioning
confidence: 99%
“…Brand equity is widely conceptualized as a distinct image consumers hold towards a particular product in the market [8]. Brand equity indicators include virtue, ability to meet functional needs, personal evaluation of customers, customer response, customer reaction, and resonance [15], [19], [25]- [28].…”
Section: All Variables Were Measured By Participants' Responses To Qu...mentioning
confidence: 99%